2002
DOI: 10.1159/000051814
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Oxidative State in Non-Lesional Skin of Atopic Dermatitis

Abstract: Background: The stratum corneum (SC), as the skin layer most exposed to various environmental factors, is particularly susceptible to oxidative stress. Due to the high lipid content of the SC, lipophilic antioxidants such as α-tocopherol are expected to play a major role in scavenging reactive oxidant intermediates produced during oxidative stress. Objectives: Since the skin of atopic dermatitis patients has an impaired barrier function, we wondered if they were more susceptible to environmental oxidative stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
3

Year Published

2003
2003
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 20 publications
0
23
0
3
Order By: Relevance
“…Alterations in antioxidant patterns, similar to those observed systemically, were found in involved skin of AD patients, whereas increased α‐tocopherol levels and decreased lipid peroxides have been found in non‐lesional skin 5 as a consequence of an adaptive response to a chronic inflammatory state of the epidermis.…”
Section: Action Of Ros and Lipids In The Development Of Skin Inflammamentioning
confidence: 55%
“…Alterations in antioxidant patterns, similar to those observed systemically, were found in involved skin of AD patients, whereas increased α‐tocopherol levels and decreased lipid peroxides have been found in non‐lesional skin 5 as a consequence of an adaptive response to a chronic inflammatory state of the epidermis.…”
Section: Action Of Ros and Lipids In The Development Of Skin Inflammamentioning
confidence: 55%
“…Positive staining with the anti-4-hydroxy-2-nonenal antibody was observed in the most superficial layers of the stratum corneum. The other group reported that the concentration of α-tocopherol in the stratum corneum was higher in scrapings of the nonlesional forearms of patients with atopic dermatitis than in samples collected from healthy control subjects [7]. However, they reported that the concentrations of lipid peroxides in the stratum corneum of the atopic dermatitis patients was slightly, but significantly, lower than that of normal controls.…”
Section: Elevation Of Reactive Oxygen Species/reactive Nitrogen Specimentioning
confidence: 96%
“…In view of the high lipid content of the stratum corneum, lipophilic antioxidants like α-tocopherol are expected to play a major role in scavenging reactive oxidant intermediates produced during oxidative stress. Two groups have directly measured the footprints of oxidative damage in the stratum corneum of patients with atopic dermatitis [6,7]. The concentrations of carbonyl moieties (markers of oxidative protein damage) were elevated in skin biopsies from 75 patients with atopic dermatitis in a manner that was directly correlated with the severity of the disease [6].…”
Section: Elevation Of Reactive Oxygen Species/reactive Nitrogen Specimentioning
confidence: 99%
“…The last hypothesis could be the regeneration of vitamin E, a lipophilic antioxidant, by AA. Indeed, Antille et al [18]have recently shown that AD patients exhibit a two-fold higher α-tocopherol concentration in the stratum corneum. Besides, Solvoll et al [19]and Barth et al [20]have shown that AD patients have a significantly lower intake of fruits than healthy controls.…”
Section: Discussionmentioning
confidence: 99%